UPAYA MENINGKATKAN KEPERCAYAAN DIRI ANAK MELALUI PENERAPAN METODE BERCERITA DI TK ISLAM KREATIF KELUARGA CERIA BERAN TRIDADI SLEMAN - Nihwan; Dhiarti Tejaningrum (STPI Bina Insan Mulia Yogyakarta, 2021)
One of the achievements of group A Early Childhood Education development is that children are able to show self-confidence. The achievement of these developments is included in each unit of daily learning plan activities which are commonly referred to as the Daily Learning Implementation Plan. However, in the implementation in the field, namely in the Kindergarten IK Keluarga Ceria, there are still children who have less self-confidence. Therefore, it is necessary to hold this research to increase the self-confidence of children as the next generation of the nation with strong personalities and to become a better generation. This study aims to determine the application of the storytelling method to group A1 children at TK IK Keluarga Ceria Beran Tridadi Sleman, and to determine the effectiveness of the storytelling method in increasing the self-confidence of group A1 children at TK IK Keluarga Ceria. The research method used is qualitative research in the form of Classroom Action Research or PTK. The research subjects were group A1 children of the Cheerful Family IK Kindergarten, totaling 19 children. Data collection was carried out by means of observation, interviews, documentation, and data analysis. The results showed that: the application of the storytelling method was able to increase the self-confidence of children in group A1 TK IK Keluarga Ceria Beran Tridadi Sleman, and the method of telling stories was effective in increasing the self-confidence of children in group A1 TKIK Keluarga Ceria Beran Tridadi Sleman. = 42%, cycle II = 84%, and cycle III = 94%.